The Effect of Jury Deliberation on the Outcome of Criminal Trials - Adedeji, Olutimilehin Adedayo (2007)
INTRODUCTION The criminal justice system is a key element in implementing the social interest in the way individuals and corporations conduct themselves. If the criminal process is to be effective in responding to criminal activity, it is essential that it leads to punishment of those who are guilty, and acquittal of those who are tried but later found to be innocent; It is only then that the criminal process implements societal intention. In particular, it is necessary to this end that the criminal processes punishes only those who are guilty. Whenever an innocent person is wrongly convicted,the criminal process falls out of line with society's intention and slips marginally into disrepute. Such miscarriages of justice come to be acknowledged only if there is (at what ever stage) a successful appeal. Appeals may succeed because of new evidence, or because of a flaw in the judges direction concerning the evidence and the law. However, there is a third element in the criminal process which generally does not form a basis of appeals, and that is the deliberation of the jury. It the role of the jury's deliberation in the criminal process that this dissertation seeks to examine. In criminal trials (and still in some civil matters) the sole judge of fact is the jury. It is not judges, but juries that decide guilt and innocence or liability. Appropriately, English law places great importance on how the jury's input is managed. - 7 - At the end of a trial, each juror has heard and seen the evidence and received direction from the judge advising them on matters of law. Each juror is then equipped to form a view as to the guilt or innocence of the accused. It may seem that the process could be ended there by a secret ballot of jurors, each expressing his or her own personal belief, however this does not occur in practice. Instead, 12 jurors retire and discuss the evidence. In other words, the jury deliberates. The deliberations are kept private and secret until the jury collectively returns a verdict. It is evident that the law believes the process of deliberation to be important, and presumably has some effect on the outcome; however ironically, the law allows us to discover nothing about the process of deliberation. The jury's deliberations are kept secret at the time and forever after. Thus we have a key stage in the process of a criminal trial which remains a closed box to researchers. There are good reasons for secrecy about the jury's deliberation in any specific trial, but there is an alterative to seeking to breach the secrecy of the jury room. In this dissertation, we set out to explore the possibilities of what might, in principle, happen in jury deliberations. A defining characteristic of the deliberation process is that it involves communications within the group of twelve jurors, whilst excluding external factors. A method of investigation of the possibilities that this may give rise to, uses Monte Carlo simulations. We begin with 12 individuals, each of whom has some degree of belief in the guilt of the defendant. These degrees of belief are generated randomly within pre-set parameters. Each individuals - 8 - degree of belief then becomes modified in a sequence of rounds of communications within the jury. For the most part, we assume that individuals are truth seeking and do not play strategic games, but are influenced by the opinions of their fellow jurors. The net outcome of this is a terminal set of degrees of belief, on the basis of which each juror votes guilty or not guilty, with reference to the judges direction as to the degree of certainty he must hold before voting guilty (the legal standard of proof). Through this model of the process of deliberation we can investigate the phenomena which might arise. Where the jurors begin their deliberation with the same (or very similar) beliefs, the verdict will eventually follow those beliefs. Therefore, the situations of interest are those with which there is a diversity of opinion. Our focus will therefore be on how differences of opinion become resolved in the deliberation process. Of most acute interest, is the possibility that in resolving the differences of opinion, there arises a reversal of opinion. If at the start of deliberation, most jurors believe the defendant not guilty, but the eventual verdict is guilty; or if an initial majority in favour of conviction leads eventually to a verdict of not guilty, then we have the most interesting situation with respects the role of deliberation. In each of those cases, deliberation (on the one hand) and a secret ballot (on the other hand) would lead to different results. We are therefore particularly interested to discover what circumstances within the jury might in principle leads to a reversal of opinion. - 9 - To address the afore mentioned issues, we will first give an overview of the jury process within a UK context in Chapter 2. With this framework in mind we review the existing literature on decision making within juries in Chapter 3 whilst highlighting some possible limitations of the existing literature with respects UK legal practice in Chapter 4. In continuation, we then explore the body of theoretical material related to interactions within small groups, and degrees of beliefs in Chapter 5. A model of beliefs or attitudes among a group of individuals is adapted from the literature on knowledge stocks and transfers to relate to juries. Chapter 5 also explores how changing sets of beliefs involves bringing together the ideas of fuzzy (or multivalent) truth values and probabilities. If beliefs among a group of people are to be modelled, we need to consider both the degree to which an individual is convinced of some proposition, and the probability of them becoming convinced to a certain degree. Having developed the theoretical models necessary to address these issues, a Monte Carlo computer simulation model is developed in Chapter 6 & 7 to assess the necessary and sufficient ingredients required to alter beliefs within a jury. Our exploration concludes with broad conclusions and Implications in Chapter 8.